BRYOPHYTES OF MOUNT PATUHA, WEST JAVA, INDONESIA - GRADSTEIN, ROBBERT; KIEN–THAI, YONG; SULEIMAN, MONICA; PUTRIKA, AFIATRI; APRIANI, DIAN; YUNIATI, ENY; KANAK, FADZILAH AG.; ULUM, FUAD BAHRUL; WAHYUNI, INDAH; WONGKUNA, KANJANA; LUBOS, LESLEY C.; TAM, LUONG THIEN; PUSPANINGRUM, MIKA RIZKI; HJ. SERUDIN, MOHD RAWIYANI PG.; ZUHRI, MUSYAROFAH; MIN, NG AIK; JUNITA, NURLISMA; PASARIBU, NURSAHARA; KORNOCHALERT, SOONTHREE (Research Center for Biology, 2010)
GRADSTEIN, R. et al. 2010. Bryophytes of Mount Patuha, West Java, Indonesia. Reinwardtia 13(2): 107-123. - This paper presents the results of a two-day survey of the bryophyte flora of Mt. Patuha and its surroundings near Bandung, West Java, carried out in the framework of the 5th regional training course on bryophyte and lichen diversity and conservation organized by SEAMEO BIOTROP, Bogor, in July 2009. A total of 159 bryophyte species were identified, including 98 mosses, 60 liverworts, and 1 hornwort, representing almost 1/6 of the total bryophyte flora of Java. Three moss species, Bryohumbertia subcomosa (Dix.) J.-P. Frahm, Fissidens gymnogynus Besch. and F. polypodioides Hedw., and one liverwort, Lejeunea pectinella Mizut., are new additions to the Javanese flora. The bryophyte diversity of Mt. Patuha is well representative of the Malesian flora and is rich in uncommon species. However, the relatively poor representation of shade epiphytes and commonness of sun epiphytes and generalists reflect disturbance of the forest by anthropogenic activities. Careful attention should be given to conservation of the remaining natural forest in order to prevent further losses of the rich bryophyte diversity of the area.